CO oxidation over Cu2O deposited on 2D continuous lamellar g-C3N4. (27th August 2015) - Shi, Yukun; Hu, Xiaojing; Zhao, Jingtao; Zhou, Xiaojiao; Zhu, Baolin; Zhang, Shoumin; Huang, Weiping
<x xml:space="preserve">Abstract</x> The changing trend of adsorption ability and the catalytic activity of Cu2O/g-C3N4 moved in the same direction.